GPS TEC variations under quiet and disturbed geomagnetic conditions during the descending phase of 24th solar cycle over the Indian equatorial and low latitude regions - Lissa, A.; Venkatesh, K.; Prasad, D.S.V.V.D.; Niranjan, K.; Seemala, Gopi K. (My University, 2021)
The present study is focused to understand the geomagnetic storm effects on the short- and long-term variations of ionospheric Total Electron Content (TEC) over the equatorial and low latitude sectors. GPS-TEC observations over a near equatorial station Bangalore and low latitude stations Waltair and Hyderabad during the declining phase of the 24th solar cycle (2015–2019) is analysed. The TEC variations during quiet and disturbed conditions are individually analysed to understand the geomagnetic storm effects on the diurnal, seasonal and solar activity variations. The seasonal variations of disturbed time TEC are following the quiet time trend with equinoctial maximum and summer minimum in the moderate solar activity periods. But, during low solar activity periods, the seasonal dependence of disturbed time TEC is different than that of quiet time. The difference in TEC during disturbed and quiet times is higher during moderate solar activity than that of low solar activity conditions. The TEC difference between disturbed and quiet periods is found to be maximum during summer months of moderate solar activity periods. Further, correlation analysis between F 10.7 cm solar flux and TEC during quiet and disturbed conditions is carried out for three different locations. It is found that the correlation between TEC and F 10.7 cm solar flux is higher during quiet time compared to that during disturbed periods with more correlation at the equator than at low latitudes.
Keywords: GPS TEC variations, Quiet geomagnetic variations, Disturbed geomagnetic variations, Indian equatorial region, Low latitude regions